Malignant Pyoderma - Mohanty Juthika; Sharma A; Sharma M.K (Wolters Kluwer Medknow Publications, 2002)
A 30 year old man presented with multiple ulcers with necrotic base over scalp, neck, presternal region. Neither any systemic disease was associated nor any abnormality by laboratory investigation was found. Patient responding well to dapsone and corticosteroid. It was designated as a case of malignant pyoderma.